Plasma modified carbon supported Pt and PtRu electrocatalyst materials for PEMFCs - Suwit Suthirakun (2018)
In this study, Pt and PtRu supported on N 2 plasma treated carbon were prepared by a simple microwave-assisted solution method using ethylene glycol as both a reducing agent and the solvent. The N 2 plasma treatment of the carbon supporter provided C-N and C = N functional groups on the surface of the carbon support which are the active sites for hydrogen oxidation and oxygen reduction reactions. Moreover, by employing microwave heated polyol, Pt and PtRu solutions can be reduced by ethylene glycol and become Pt metal or PtRu alloy on the carbon support. Depending on these procedures and physical and electrochemical characterizations, Pt and PtRu supported on plasma treated carbon were obtained and their catalytic activity studied. X-ray diffraction patterns of the catalysts prepared indicated the crystallographic structure of Pt/C and PtRu/C. TEM images of the catalysts prepared showed the particle size of Pt/C catalysts to be about 1.67 nm and for the PtRu/C catalyst it was about 1.04 nm. The catalysts prepared were homogeneously distributed on the carbon supports. Among the catalysts prepared and commercial Pt catalysts, PtRu catalyst supported on plasma treated carbon showed the highest electrochemical activity.